High-density supported polymetallic particles on a chemically modified carbon support.
Patent Information
- Application Number
- JP2026049478
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-03-24
- Publication Date
- 2026-10-14
Smart Images

Figure 2026167564000004 
Figure 2026167564000005 
Figure 2026167564000006
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to supported multimetallic particles.
BACKGROUND ART
[0002] Multimetallic materials have been demonstrated to exhibit significant lattice strain and excellent corrosion resistance, making them attractive candidates for use in energy conversion and storage applications such as fuel cell catalysts. However, current attempts to deposit such catalysts on supports are ineffective, impeding the improvement of loading density and limiting the effectiveness and service life of the catalysts.
SUMMARY OF THE INVENTION
MEANS FOR SOLVING THE PROBLEMS
[0003] Disclosed herein is a method for preparing multimetallic particles on a support. The method may comprise the steps of mixing two or more metal precursors in a solvent with the support to form a suspension, and heating the suspension to form the multimetallic particles on the support. According to some embodiments, the support may comprise carbon particles. The present disclosure also relates to the supported multimetallic particles described herein.
BRIEF DESCRIPTION OF THE DRAWINGS
[0004] [Figure 1A] The XRD pattern corresponding to the supported multimetallic nanoparticles of Example I(a) is shown.
[0005] [Figure 1B] The XRD pattern corresponding to the supported multimetallic nanoparticles of Example I(b) is shown.
[0006] [Figure 1C] The XRD pattern corresponding to the supported multimetallic nanoparticles of Example I(c) is shown.
[0007] [Figure 2A] The TEM photograph of the supported multimetallic nanoparticles of Example I(a) is shown.
[0008] [Figure 2B] The TEM photograph of the supported multimetallic nanoparticles of Example I(b) is shown.
[0009] [Figure 2C] The TEM photograph of the supported multimetallic nanoparticles of Example I(c) is shown.
[0010] [Figure 2D] The TEM photograph of the supported multimetallic nanoparticles of Example II is shown.
[0011] [Figure 3A] The EDA spectrum of the supported multimetallic nanoparticles of Example I(a) is shown.
[0012] [Figure 3B] The EDA spectrum of the supported multimetallic nanoparticles of Example I(b) is shown.
[0013] [Figure 3C] The EDA spectrum of the supported multimetallic nanoparticles of Example I(c) is shown.
[0014] [Figure 4A] The ORR polarization curve of the supported multimetallic nanoparticles of Example I(a) is shown.
[0015] [Figure 4B] The ORR polarization curve of the supported multimetallic nanoparticles of Example I(b) is shown.
[0016] [Figure 4C] The ORR polarization curve of the supported multimetallic nanoparticles of Example I(c) is shown.
[0017] [Figure 5] The specific surface area activity of multimetallic nanoparticles supported on various modified carbons is shown. [Mode for Carrying Out the Invention]
[0018] Disclosed herein is a method of preparing multimetallic particles on a support. The method may comprise the steps of mixing two or more metal precursors in a solvent with a support to form a suspension, and heating the suspension to form multimetallic particles on the support. According to some embodiments, the support may comprise carbon particles. The present disclosure also relates to supported multimetallic particles prepared by the methods disclosed herein.
[0019] As used herein, "multimetallic particles" are particles containing two or more different metal elements. In some non-limiting examples, the multimetallic particles may comprise a high-entropy alloy or "HEA". As used herein, the term "high-entropy alloy" or "HEA" generally refers to an alloy having two or more metal elements with a mixing entropy greater than 1.3R, wherein the mixing entropy is determined using the formula ΔSmix=RlnN, where R is the gas constant and N is the total number of elements.
[0020] According to some embodiments, each of the two or more different metal elements contained in the multimetallic particles may independently be Pt, Ru, Co, Fe, Ni, Ir, Y, Cu, Rh, and Ag. According to some embodiments, the multimetallic particles may comprise 2, 3, 4, 5, 6 or more different metal elements, as described herein. According to some embodiments, the multimetallic particles may comprise an alloy crystalline phase, that is, a single phase formed from an alloy of two or more different metal elements, in which the atoms of the alloy are arranged in a substantially regular pattern.
[0021] In some non-limiting examples, the polymetallic particles may include Pt, Ru, Co, Fe, and Ni. In some non-limiting examples, the polymetallic particles may include Pt, Ru, Co, and Ni. In some non-limiting examples, the polymetallic particles may include Ir, Ru, Co, Fe, and Ni. In some non-limiting examples, the polymetallic particles may include Ir, Ru, Co, and Ni. In some non-limiting examples, the polymetallic particles may include Ag, Ru, Co, Fe, and Ni. In some non-limiting examples, the polymetallic particles may include Ag, Ru, Co, and Ni.
[0022] According to some embodiments, each of the two or more different metallic elements contained in the polymetallic particle may be present in the polymetallic particle independently in an amount of about 0.01 to 50 atomic percent.
[0023] In some non-limiting examples, polymetallic particles may contain at least one metallic element in amounts of about 0.1–10 atomic%, optionally about 0.1–5 atomic%, and optionally about 1–5 atomic%.
[0024] In some non-limiting examples, polymetallic particles may contain at least one metal element in amounts of approximately 5–25 atomic%, optionally about 10–20 atomic%, optionally about 10–15 atomic%, and optionally about 15–20 atomic%.
[0025] In some non-limiting examples, polymetallic particles may contain at least one metal element in amounts of approximately 30–50 atomic%, optionally approximately 35–45 atomic%, optionally approximately 35–40 atomic%, and optionally approximately 40–45 atomic%.
[0026] The relative amounts of each metal element may vary individually with respect to at least one other metal element contained in the polymetallic particle, within ±50 atomic% of the specified limit, optionally within ±40 atomic% of the specified limit, optionally within ±30 atomic% of the specified limit, optionally within ±25 atomic% of the specified limit, optionally within ±20 atomic% of the specified limit, or optionally within ±15 atomic% of the specified limit.
[0027] In some embodiments, the polymetallic particles disclosed herein may include polymetallic nanoparticles. As used herein, the term “nanoparticle” refers to a particle having at least one dimension on the nanoscale (i.e., at least one dimension between about 0.1 and 100 nm). In some non-limiting examples, nanoparticles may include particles whose spatial dimensions are on the nanoscale.
[0028] The polymetallic particles of this disclosure are formed on a carrier, thereby forming supported polymetallic particles. According to some embodiments, the supported polymetallic particles may include chemical bonds between the polymetallic particles and the carrier, such as ionic bonds, covalent bonds, metallic bonds, hydrogen bonds, or combinations thereof. The carrier may include particles of the carrier material (including, but not limited to, nanoparticles). In some non-limiting examples, the carrier material may include carbon, such as carbon black.
[0029] In some embodiments, the carbon may include modified carbon. As used herein, the term “modified carbon” refers to carbon that has been modified to have one or more functional groups, each containing a non-carbon element. The non-carbon element may include, for example, O, S, N, or combinations thereof. In some non-limiting examples, one or more functional groups may include aromatic functional groups. Exemplary functional groups include, but are not limited to, phenol, thiophenol, aniline, amine, carboxylate, hydroxyl, thiol, and combinations thereof. In some embodiments, the support may include modified carbon black.
[0030] In some embodiments, the supported polymetallic particles may contain metal elements in a specific mass ratio to the carrier material disclosed herein. For example, if the carrier contains modified carbon black, the supported polymetallic particles may contain metal elements in a specific mass ratio to carbon. In some embodiments, the mass ratio may be about 1:1 to 100:1, optionally about 1:1 to 60:1, optionally about 1:1 to 50:1, optionally about 1:1 to 40:1, optionally about 1:1 to 30:1, optionally about 1:1 to 20:1, or optionally about 10:1. In some embodiments, the mass ratio may be at least about 1:1, optionally at least about 5:1, optionally at least about 10:1, optionally at least about 15:1, optionally at least about 20:1, optionally at least about 25:1, optionally at least about 30:1, optionally at least about 35:1, optionally at least about 40:1, optionally at least about 45:1, optionally at least about 50:1, optionally at least about 55:1, or optionally at least about 60:1.
[0031] A method for preparing polymetallic particles on a carrier described herein is disclosed herein. The method may include the steps of: mixing two or more metal precursors in a solvent with a carrier to form a suspension; and heating the suspension to form polymetallic particles on the carrier.
[0032] Each metal precursor may contain a metal element as described herein. In some embodiments, each metal precursor may contain a compound having a metal element. In some non-limiting examples, the compound may be an organic salt of a metal, such as a metal acetylacetonate, a metal acetate salt, a metal stearate salt, or a combination thereof.
[0033] The solvent may include glycols. In some non-limiting examples, the glycols may have a boiling point of at least about 200°C. Non-limiting examples of useful glycols according to this disclosure include ethylene glycol, tetraethylene glycol, hexaethylene glycol, glycerin, pentaethylene glycol, and combinations thereof.
[0034] The method may include the step of mixing two or more metal precursors independently with a solvent, either simultaneously or sequentially with at least one of the other metal precursors. In some embodiments, the method may include the step of dispersing the two or more metal precursors in the solvent by stirring for a certain period of time. It should be understood that "stirring" as used herein may include sonication, mixing, stirring, shaking, etc. In some non-limiting examples, the time may be about 1 minute to 1 hour, optionally about 1 minute to 30 minutes, optionally about 1 minute to 20 minutes, or optionally about 10 minutes.
[0035] The method may include the step of mixing two or more metal precursors in a solvent with a carrier disclosed herein. In some embodiments, the carrier may be provided as a carrier suspension. For example, the method may include the step of preparing the carrier disclosed herein with a solvent and stirring for a certain period of time to form a carrier suspension. The solvent may be the same as or different from the solvent used to mix the two or more metal precursors described herein. In some embodiments, the time may be about 1 minute to 1 hour, optionally about 15 minutes to 45 minutes, or optionally about 30 minutes.
[0036] In some embodiments, two or more metal precursors in a solvent may be gradually mixed with a carrier and / or carrier suspension over a set period of time to form a suspension. In some non-limiting examples, the time may be at least 1 minute, optionally at least 10 minutes, or optionally at least about 20 minutes. The two or more metal precursors, the solvent, and the carrier and / or carrier suspension may be stirred for part or all of the set period of time.
[0037] The method may further include the step of heating the suspension to a certain high temperature for a certain period of time sufficient to form the supported polymetallic particles disclosed herein. According to some embodiments, the heating may be carried out in a reduced-pressure environment, such as an autoclave. As used herein, “reduced-pressure environment” refers to an environment in which the pressure is lower than the mean atmospheric pressure at sea level on Earth.
[0038] In some embodiments, the constant high temperature may be approximately 100 to 260°C, optionally 100 to 250°C, optionally 110 to 230°C, or optionally 120 to 220°C. In some embodiments, the constant high temperature may be less than approximately 250°C, optionally less than approximately 230°C, or optionally less than approximately 220°C. In some embodiments, the constant time may be approximately 1 to 54 hours, or optionally about 6 to 48 hours.
[0039] In some embodiments, heating may be carried out in a furnace. In some embodiments, heating may be carried out without microwave heating. Additionally or alternatively, heating may be carried out without ultrasonic heating. However, the disclosure is not necessarily limited in this way, as heating may be carried out additionally or alternatively with microwave heating, ultrasonic heating, or a combination thereof.
[0040] This method may further include a certain cooling period in which heating is stopped and the suspension is cooled to approximately room temperature, i.e., approximately 20-22°C. The cooling period may be at least 1 hour, optionally at least 2 hours, optionally at least 3 hours, optionally at least 4 hours, optionally at least 5 hours, or optionally at least 6 hours.
[0041] The method may further include one or more washing steps sufficient to separate the supported polymetallic particles from unreacted precursors, solvents, and / or other by-products. In some non-limiting examples, each washing step may independently include one or more of the steps of decanting the supernatant, adding one or more solvents, and / or sonication. According to some embodiments, the solvent may include isopropanol, methanol, ethanol, acetone, water, or a combination thereof. Each washing step may independently further include the steps of centrifugation and discarding the resulting supernatant. According to some embodiments, the synthesis process may include one, two, three, or more washing steps. The method may further include the step of drying the resulting supported polymetallic particles.
[0042] The supported polymetallic particles of this disclosure may be useful for fuel cell applications such as fuel cell catalysts. Accordingly, this disclosure also relates to fuel cells comprising the supported polymetallic particles described herein. In some non-limiting examples, a fuel cell may comprise an anode comprising an anode material and a cathode comprising a cathode material, wherein at least one of the anode material and the cathode material comprises the supported polymetallic particles described herein. The fuel cell may further comprise an electrolyte. In some non-limiting examples, the electrolyte may comprise an acidic electrolyte, such as in a photoelectrochemical cell.
[0043] While the embodiments described herein are explained in conjunction with the exemplary embodiments outlined above, various substitutes, variations, modifications, improvements, and / or substantial equivalents, whether known or currently unpredictable, will be apparent to those skilled in the art. Therefore, such exemplary embodiments are intended to be illustrative, not limiting. Various modifications can be made without departing from the spirit and scope of this disclosure. Accordingly, this disclosure is intended to encompass all known or future-developed substitutes, variations, modifications, improvements, and / or substantial equivalents.
[0044] Accordingly, the claims are not intended to be limited to the embodiments shown herein, but rather to be given the full scope consistent with the language of the claims, and references to singular elements are intended to mean "one or more" and not "one and only" unless otherwise specified. All structural and functional equivalents to elements of various embodiments described throughout this disclosure, whether known to those skilled in the art or to become known thereafter, are expressly incorporated herein by reference and are intended to be included in the claims. Furthermore, nothing disclosed herein is intended to be made available to the public, whether such disclosure is expressly stated in the claims. Elements of the claims should not be interpreted as means plus function unless they are expressly referred to using the phrase "means for".
[0045] In this specification, descriptions of numerical ranges using endpoints (e.g., about 50:1 to 1:1, about 100 to 500°C, about 1 minute to 60 minutes) include all numbers within that range. For example, about 1 minute to 60 minutes includes 21 minutes, 22 minutes, 23 minutes, and 24 minutes as endpoints within the specified range. Therefore, ranges such as 22 to 36, 25 to 32, 23 to 29, etc., are also ranges whose endpoints are included within range 1 to 60, depending on the starting materials used, temperature, specific application, specific embodiment, or, if necessary, limitations of the claims. The examples and methods disclosed herein demonstrate that the described ranges include all points within the range, as different synthetic products are produced after changing one or more reaction parameters. Furthermore, the methods and examples disclosed herein illustrate various aspects of the disclosed ranges and the effects of changing the ranges individually or in combination with other described ranges.
[0046] Furthermore, the word “example” is used herein to mean “to serve as an example, illustration, or empirical example.” Any embodiment described herein as “example” should not necessarily be construed as being preferable or more advantageous than other embodiments. Unless otherwise specified, the term “several” means one or more. Combinations such as “at least one of A, B, or C,” “at least one of A, B, and C,” and “A, B, C, or any combination thereof” include any combination of A, B, and / or C, and may include multiple A, multiple B, and multiple C. Specifically, combinations such as “at least one of A, B, or C,” “at least one of A, B, and C,” and “A, B, C, or any combination thereof” may be A only, B only, C only, A and B, A and C, B and C, or A and B and C, and any of these combinations may include one or more A, B, or C. Nothing disclosed herein is intended to be made available to the public, whether such disclosure is expressly stated in the claims or not.
[0047] As used herein, the terms “about” and “approximately” are defined as close as those skilled in the art would understand. In one non-limiting embodiment, the terms “about” and “approximately” are defined as within 10%, preferably within 5%, more preferably within 1%, and most preferably within 0.5%.
[0048] These examples are provided to those skilled in the art to provide a complete disclosure and explanation of the manufacturing method and use of the present invention, and are not intended to limit the scope of what the inventors consider to be the invention, nor to indicate that the following experiments are all or only experiments performed. While efforts have been made to ensure accuracy with respect to the figures used (e.g., quantities, dimensions, etc.), some experimental error and deviation should be taken into consideration. [Examples]
[0049] Example I(a): Direct synthesis of PtNiCoRu alloy nanoparticles on thiophenol-modified XC-72 carbon black
[0050] First, 40 mg each of Pt(acac)2, Ru(acac)3, Co(acac)3, Ni(acac)2, and Fe(acac)3 were sonicated in 8 mL of ethylene glycol for 10 minutes. Next, 20 mg of thiophenol-modified Vulcan XC-72 carbon black was dispersed in 10 mL of ethylene glycol (EG) for 30 minutes to prepare a carrier suspension, forming a homogeneous carbon-EG suspension due to the high viscosity of the solvent. Then, 2 mL of the carrier suspension was gradually added to the precursor mixture with vigorous stirring for at least 20 minutes. Subsequently, the well-mixed black suspension containing all the precursors and carbon black was transferred to a 100 mL autoclave in an oven. The entire reactor was heated to the design temperature (approximately 120°C to 220°C) and maintained at that temperature for a set period (approximately 6 to 48 hours). Following the reaction steps, the reactor was cooled to room temperature (approximately 20°C) over approximately 6 hours. To remove excess unreacted precursor, solvent, and other by-products, the supernatant was decanted and 25 mL of isopropanol was added. To remove adsorbed solvent molecules, the product was sonicated in isopropanol for 30 minutes. Next, the carbon product was centrifuged at 8000 rpm for 20 minutes. If necessary, another 20 minutes of centrifugation at 8000 rpm was performed. The black precipitate was washed by adding isopropanol or water while sonicating for 30 minutes. The precipitate was centrifuged at 7000 rpm for 15 minutes. The washing procedure was repeated at least twice. Subsequently, the precipitate from the suspension was dried in a vacuum oven before further characterization and application.
[0051] Example I(b): Direct synthesis of PtNiCoRuFe alloy nanoparticles on aniline-modified XC-72 carbon black
[0052] First, 40 mg each of Pt(acac)2, Ru(acac)3, Co(acac)3, Ni(acac)2, and Fe(acac)3 were sonicated in 8 mL of ethylene glycol for 10 minutes. Next, 20 mg of aniline-modified Vulcan XC-72 carbon black was dispersed in 10 mL of ethylene glycol (EG) for 30 minutes to prepare a carrier suspension, forming a homogeneous carbon-EG suspension due to the high viscosity of the solvent. Then, 2 mL of the carrier suspension was gradually added to the precursor mixture with vigorous stirring for at least 20 minutes. Subsequently, the well-mixed black suspension containing all the precursors and carbon black was transferred to a 100 mL autoclave in an oven. The entire reactor was heated to the design temperature (approximately 120°C to 220°C) and maintained at that temperature for a set period (approximately 6 to 48 hours). Following the reaction steps, the reactor was cooled to room temperature (approximately 20°C) over approximately 6 hours. To remove excess unreacted precursor, solvent, and other by-products, the supernatant was decanted and 25 mL of isopropanol was added. To remove adsorbed solvent molecules, the product was sonicated in isopropanol for 30 minutes. Next, the carbon product was centrifuged at 8000 rpm for 20 minutes. If necessary, another 20 minutes of centrifugation at 8000 rpm was performed. The black precipitate was washed by adding isopropanol or water while sonicating for 30 minutes. The precipitate was centrifuged at 7000 rpm for 15 minutes. The washing procedure was repeated at least twice. Subsequently, the precipitate from the suspension was dried in a vacuum oven before further characterization and application.
[0053] Example I(c): Direct synthesis of PtNiCoRu alloy nanoparticles on phenol-modified XC-72 carbon black
[0054] First, 40 mg each of Pt(acac)2, Ru(acac)3, Co(acac)3, Ni(acac)2, and Fe(acac)3 were sonicated in 8 mL of ethylene glycol for 10 minutes. Next, 20 mg of phenol-modified Vulcan XC-72 carbon black was dispersed in 10 mL of ethylene glycol (EG) for 30 minutes to prepare a carrier suspension, forming a homogeneous carbon-EG suspension due to the high viscosity of the solvent. Then, 2 mL of the carrier suspension was gradually added to the precursor mixture with vigorous stirring for at least 20 minutes. Subsequently, the well-mixed black suspension containing all the precursors and carbon black was transferred to a 100 mL autoclave in an oven. The entire reactor was heated to the design temperature (approximately 120°C to 220°C) and maintained at that temperature for a set period (approximately 6 to 48 hours). Following the reaction steps, the reactor was cooled to room temperature (approximately 20°C) over approximately 6 hours. To remove excess unreacted precursor, solvent, and other by-products, the supernatant was decanted and 25 mL of isopropanol was added. To remove adsorbed solvent molecules, the product was sonicated in isopropanol for 30 minutes. Next, the carbon product was centrifuged at 8000 rpm for 20 minutes. If necessary, another 20 minutes of centrifugation at 8000 rpm was performed. The black precipitate was washed by adding isopropanol or water while sonicating for 30 minutes. The precipitate was centrifuged at 7000 rpm for 15 minutes. The washing procedure was repeated at least twice. Subsequently, the precipitate from the suspension was dried in a vacuum oven before further characterization and application.
[0055] Example II: Direct synthesis of PtNiCoRu alloy nanoparticles on unmodified XC-72 carbon black
[0056] First, 40 mg each of Pt(acac)2, Ru(acac)3, Co(acac)3, Ni(acac)2, and Fe(acac)3 were sonicated in 8 mL of ethylene glycol for 10 minutes. Next, 20 mg of unmodified Vulcan XC-72 carbon black was dispersed in 10 mL of ethylene glycol (EG) for 30 minutes to prepare a carrier suspension, forming a homogeneous carbon-EG suspension due to the high viscosity of the solvent. Then, 2 mL of the carrier suspension was gradually added to the precursor mixture with vigorous stirring for at least 20 minutes. Subsequently, the well-mixed black suspension containing all the precursors and carbon black was transferred to a 100 mL autoclave in an oven. The entire reactor was heated to the design temperature (approximately 120°C to 220°C) and maintained at that temperature for a set period (approximately 6 to 48 hours). Following the reaction steps, the reactor was cooled to room temperature (approximately 20°C) over approximately 6 hours. To remove excess unreacted precursor, solvent, and other by-products, the supernatant was decanted and 25 mL of isopropanol was added. To remove adsorbed solvent molecules, the product was sonicated in isopropanol for 30 minutes. Next, the carbon product was centrifuged at 8000 rpm for 20 minutes. If necessary, another 20 minutes of centrifugation at 8000 rpm was performed. The black precipitate was washed by adding isopropanol or water while sonicating for 30 minutes. The precipitate was centrifuged at 7000 rpm for 15 minutes. The washing procedure was repeated at least twice. Subsequently, the precipitate from the suspension was dried in a vacuum oven before further characterization and application.
[0057] Example III: XRD characterization of supported polymetallic nanoparticles
[0058] X-ray diffraction (XRD) patterns of supported polymetallic nanoparticles prepared according to Examples I(a) to I(c) were obtained using a Bruker D8 Advance X-ray diffractometer operating at a tube voltage of 40 kV and a current of 40 mA, using CuKα radiation. Figure 1A shows the XRD pattern corresponding to the supported polymetallic nanoparticles of Example I(a). Figure 1B shows the XRD pattern corresponding to the supported polymetallic nanoparticles of Example I(b). Figure 1C shows the XRD pattern corresponding to the supported polymetallic nanoparticles of Example I(c). From these XRD patterns, it was concluded that the polymetallic nanoparticles contain an alloy crystalline phase rather than a mixture of individual metal phases, and considering their stability against acidic corrosion, they are suitable candidates for use in acidic electrolysis.
[0059] Example IV: TEM Characterization of Supported Multimetallic Nanoparticles
[0060] Transmission electron microscope (TEM) images of supported polymetallic nanoparticles prepared according to Examples I(a) to I(c) and II were taken using an FEI Tecnai 20 microscope with an acceleration voltage of 200 kV. Figure 2A shows the TEM image of the supported polymetallic nanoparticles of Example I(a). Figure 2B shows the TEM image of the supported polymetallic nanoparticles of Example I(b). Figure 2C shows the TEM image of the supported polymetallic nanoparticles of Example I(c). Figure 2D shows the TEM image of the supported polymetallic nanoparticles of Example II.
[0061] As shown in Figures 2A to 2D, the supported polymetallic nanoparticles of Examples I(a) and I(b) exhibited ultra-high density support of polymetallic nanoparticles on the support. Furthermore, the supported polymetallic nanoparticles of Example I(c) showed a higher density support than the supported polymetallic nanoparticles of Example II.
[0062] Example V: EDS characterization of supported polymetallic nanoparticles
[0063] Energy-dispersive X-ray spectra (EDS) of supported polymetallic nanoparticles prepared according to Examples I(a) to I(c) were collected by FEI SEM. Figure 3A shows the EDA spectrum of the supported polymetallic nanoparticles of Example I(a). Figure 3B shows the EDA spectrum of the supported polymetallic nanoparticles of Example I(b). Figure 3C shows the EDA spectrum of the supported polymetallic nanoparticles of Example I(c).
[0064] Based on these spectra, the composition of each supported polymetallic nanoparticle prepared according to Examples I(a) to I(c) was determined as shown in Tables 1 to 3. [Table 1] [Table 2] [Table 3]
[0065] Example VI: Electrochemical property evaluation of supported polymetallic nanoparticles
[0066] Most electrochemical measurements were performed on an electrochemical workstation at ambient temperature (25°C) using a three-electrode electrochemical setup with a rotating disk electrode (RDE). All experiments utilized a glassy carbon working electrode (GCE, 5mm inner diameter, 0.196cm²). 2 A graphite rod counter electrode and a KCl-saturated Ag / AgCl reference electrode were used. All potentials were referenced to the reversible hydrogen electrode (RHE). The potential at the zero current point was selected as the reaction potential of the hydrogen electrode. The potential at the zero current point was established as -0.258V. Therefore, the potential measured at the Ag / AgCl electrode can be expressed as E(RHE) = E(Ag / AgCl) + 0.258V.
[0067] To perform the measurements, electrodes were first prepared by directly drop-casting 10 μL of solution containing particles from each of Examples I(a) to I(c) onto a glassy carbon electrode. Next, cyclic voltammograms were obtained to measure ECSA. Cyclic voltammograms (CVs) can readily reflect changes in surface structure. Therefore, CVs were used to determine the reconstruction of the surface structure. In the corresponding ranges (0 to 1.05 V, 0.025 to 1.1 V, and 0.025 to 1.3 V relative to RHE), 50 mV s was measured in an Ar-saturated 0.1 M HClO4 solution. -1 Cyclic voltammetry scans were performed at the specified scan speed. 2.5 cycles of CV were recorded to obtain reproducible cycles. High-voltage oxidation (1.3–1.5V) treatment was found to reactivate the catalyst surface that had become inactive during long-term durability testing by forming new reactive crystal planes.
[0068] The ORR polarization curve was mainly obtained at a rotation speed of 1600 rpm and a scan speed of 10 mV / s. -1 The measurements were then taken in an O2-saturated 0.1M HClO4 electrolyte. After each designed durability test, the ORR polarization curve was remeasured under the same conditions as the initial measurement. Figure 4A shows the ORR polarization curve of the supported polymetallic nanoparticles of Example I(a). Figure 4B shows the ORR polarization curve of the supported polymetallic nanoparticles of Example I(b). Figure 4C shows the ORR polarization curve of the supported polymetallic nanoparticles of Example I(c). Based on these curves, it was found that all three supported polymetallic nanoparticles have the potential to perform well in fuel cell reactions.
[0069] Figure 5 shows the specific surface area activity of polymetallic nanoparticles supported on various modified carbons, as described in Examples I(a) to I(c). The activity is calculated by normalizing the reaction current at 0.9 V with the electrochemically active surface area.
Claims
1. A method for preparing polymetallic particles on a carrier, The process involves mixing two or more metal precursors, including a first metal precursor and a second metal precursor, in a solvent with a carrier containing modified carbon to form a suspension. The steps include heating the suspension to form supported polymetallic particles, which include polymetallic particles bound to the carrier, and Methods that include...
2. The method according to claim 1, wherein the first metal precursor comprises a first metal element selected from Pt, Ru, Co, Fe, Ni, Ir, and Ag.
3. The method according to claim 2, wherein the second metal precursor comprises a second metal element selected from Pt, Ru, Co, Fe, Ni, Ir, and Ag, which is different from the first metal element.
4. The method according to claim 1, wherein the modified carbon includes modified carbon black.
5. The method according to claim 1, wherein the modified carbon includes phenol.
6. The method according to claim 1, wherein the modified carbon comprises thiophenol.
7. The method according to claim 1, wherein the modified carbon includes aniline.
8. The method according to claim 1, wherein the supported polymetallic particles have a mass ratio of metal elements to carbon of at least about 1:
1.
9. The method according to claim 1, wherein the supported polymetallic particles have a mass ratio of metal element to carbon of about 1:1 to 60:
1.
10. The method according to claim 1, wherein the suspension is heated to a temperature of about 100 to 260°C.
11. The method according to claim 1, wherein the heating is performed without microwave heating or ultrasonic heating.
12. The method according to claim 1, wherein the solvent comprises glycol.
13. The method according to claim 1, wherein the polymetallic particles include an alloy crystalline phase.
14. The method according to claim 1, wherein the polymetallic particles include a high-entropy alloy.
15. Supported polymetallic particles comprising polymetallic particles bonded to a carrier, wherein the polymetallic particles comprise a first metal element and a second metal element, and the carrier comprises modified carbon.
16. The supported polymetallic particle according to claim 15, wherein the first metal element is selected from Pt, Ru, Co, Fe, Ni, Ir, and Ag, and the second metal element is selected from Pt, Ru, Co, Fe, Ni, Ir, and Ag, in contrast to the first metal element.
17. The supported polymetallic particle according to claim 15, wherein the mass ratio of the supported polymetallic particle to the metal element is at least about 1:
1.
18. The supported polymetallic particle according to claim 15, wherein the mass ratio of the supported polymetallic particle to the metal element is about 1:1 to 60:
1.
19. The supported polymetallic particles according to claim 15, wherein the polymetallic particles include an alloy crystalline phase.
20. The supported polymetallic particles according to claim 15, wherein the polymetallic particles include a high-entropy alloy.